2009
DOI: 10.1515/forum.2009.018
|View full text |Cite
|
Sign up to set email alerts
|

On the classification of infinite-dimensional irreducible Hermitian-symmetric affine coadjoint orbits

Abstract: In the finite-dimensional setting, every Hermitian-symmetric space of compact type is a coadjoint orbit of a finite-dimensional Lie group. It is natural to ask whether every infinite-dimensional Hermitiansymmetric space of compact type, which is a particular example of an Hilbert manifold, is transitively acted upon by a Hilbert Lie group of isometries. In this paper we give the classification of infinitedimensional irreducible Hermitian-symmetric affine coadjoint orbits of L * -groups of compact type using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Then, the operator that transform the right algebra to its dual algebra is given by: (190) As there is an operator to change the view of algebra, there is one that did the same on the dual algebra, the co-adjoint operator that is the conjugate action of Lie group on its dual algebra: (191) We can then develop this expression for our use case of affine sup-group, we find: (192) and we can also observed that: (193) And the following relation between the left and the right algebras:…”
Section: Figure 10 Affine Lie Group Action For Multivariate Gaussianmentioning
confidence: 99%
“…Then, the operator that transform the right algebra to its dual algebra is given by: (190) As there is an operator to change the view of algebra, there is one that did the same on the dual algebra, the co-adjoint operator that is the conjugate action of Lie group on its dual algebra: (191) We can then develop this expression for our use case of affine sup-group, we find: (192) and we can also observed that: (193) And the following relation between the left and the right algebras:…”
Section: Figure 10 Affine Lie Group Action For Multivariate Gaussianmentioning
confidence: 99%
“…This last property allows to determine all homogeneous spaces of a Lie group admitting an invariant symplectic structure by the action of this group: there are the orbits of the coadjoint representation of this group or of a central extension of this group (the central extension allowing to suppress the cocycle). For affine coadjoint orbits, we give reference to Alice Tumpach PhD [189,190,191] that has developed previous works of K.H. Neeb, O. Biquard and P. Gauduchon.…”
Section: Resultsmentioning
confidence: 99%
“…This last property allows us to determine all homogeneous spaces of a Lie group admitting an invariant symplectic structure by the action of this group: for example, there are the orbits of the coadjoint representation of this group or of a central extension of this group (the central extension allowing suppressing the cocycle). For affine coadjoint orbits, we make reference to Alice Tumpach Ph.D. [197][198][199] who has developed previous works of Neeb [200], Biquard and Gauduchon [201][202][203][204].…”
Section: Discussionmentioning
confidence: 99%